2007
DOI: 10.1136/adc.2007.117614
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal nasal intermittent positive pressure ventilation: what do we know in 2007?

Abstract: Although neonatal nasal intermittent positive pressure ventilation (NIPPV) is widely used today, its place in neonatal respiratory support is yet to be fully defined. Current evidence indicates that NIPPV after extubation of very premature infants reduces the rate of reintubation. However, much is still not known about NIPPV including its mechanisms of action. It may improve pulmonary mechanisms, tidal volume and minute ventilation but more studies are required to confirm these findings. There is some evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 66 publications
0
29
0
4
Order By: Relevance
“…Atualmente observa-se o aumento no interesse científico e clínico pelo tipo de suporte não invasivo denominado de ventilação por pressão positiva intermitente nasal (VPPIN) [5][6][7] . Esta modalidade de ventilação é conceituada como o método de fornecimento de pressão positiva sem a necessidade de utilização de tubo intratraqueal ou traqueostomia, na qual é proporcionado suporte inspiratório de forma intermitente e não invasiva, com nível de pressão positiva inspiratória maior que a expiratória 8 .…”
Section: Introductionunclassified
“…Atualmente observa-se o aumento no interesse científico e clínico pelo tipo de suporte não invasivo denominado de ventilação por pressão positiva intermitente nasal (VPPIN) [5][6][7] . Esta modalidade de ventilação é conceituada como o método de fornecimento de pressão positiva sem a necessidade de utilização de tubo intratraqueal ou traqueostomia, na qual é proporcionado suporte inspiratório de forma intermitente e não invasiva, com nível de pressão positiva inspiratória maior que a expiratória 8 .…”
Section: Introductionunclassified
“…NIPPV ϭ nasal intermittent positive-pressure ventilation and in the need for invasive ventilation for the preterm infant. [1][2][3][4][5][6]17,18 In the present study, a significant association was observed between NIV failure and the absence of intermittent positive pressure (P ϭ .02, odds ratio 1.22). Only 30% (n ϭ 12) of the infants treated with NIPPV failed this modality.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, the use of synchronization is an important issue that needs additional investigation. 18 In the United Kingdom, given the widespread use of (S)NIPPV, not surprisingly, a wide variety of ventilator settings have been used. 6 One would anticipate a similar scenario in the units in USA using this technique.…”
Section: Techniquementioning
confidence: 99%